Self‐rated health scores predict mortality among people with type 2 diabetes differently across three different country groupings: findings from the ADVANCE and ADVANCE‐ON trials - Hua, X; Lung, TWC; Woodward, M; Salomon, JA; Hamet, P; Harrap, SB; Mancia, G; Poulter, N; Chalmers, J; Clarke, PM (Wiley, 2020)
Aims To explore whether there is a different strength of association between self‐rated health and all‐cause mortality in people with type 2 diabetes across three country groupings: nine countries grouped together as 'established market economies'; Asia; and Eastern Europe.